Pseudo-homogeneous kinetic model for esterification of acetic acid with propanol isomers over dodecatungstophosphoric acid supported on montmorillonite k10 - Gurav, Hanumant R.; Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Journal of Physical Organic Chemistry, 2014)
Esterification of acetic acid with propanol isomers such as isopropanol and naEuropropanol was carried out over dodecatungstophosphoric acid (DTPA), dodecamolybdophosphoric acid ammonium salt hydrate, and sodium tungstate hydrated purified supported on montmorillonite K10, which were characterized by powder XaEuroray diffraction, BrunaueraEuro'EmmettaEuro'Teller, and temperature programmed ammonia desorption. A pseudoaEurohomogeneous (PaEuroH) kinetic model was established for esterification of acetic acid with propanol isomers over DTPA supported on montmorillonite K10. Effects of various parameters such as reaction time, speed of agitation, particle size, temperature, percent catalyst loading, molar ratio and mixture of propanol isomer were investigated in detail. The 20% (w/w) DTPA/K10 was found to be an optimum solid catalyst with 82% naEuropropanol and 53% isopropanol conversion with 100% selectivity toward propyl acetate. The 20% (w/w) DTPA/K10 catalyst was found to be reusable for three cycles. The reaction follows secondaEuroorder kinetics with activation energies of 25.53aEuro?kJaEuro?mol(a?'1) and 28.15aEuro?kJaEuro?mol(a?'1) for isopropanol and naEuropropanol, respectively. PseudoaEurohomogeneous kinetic model fitted with R-2 value of trend line 0.999. This implies that esterification reaction is kinetically controlled owing to high activation energy. Copyright a (c) 2013 John Wiley & Sons, Ltd.
Keywords: Acetic acid; dodecatungstophosphoric acid; Esterification; kinetic model; montmorillonite K10

Benzylation of acetic acid to benzyl acetate over highly active and reusable micro/meso-HZSM-5 - Nandiwale, Kakasaheb Y.; Galande, Nitish D.; Raut, Sunil A.; Bokade, Vijay V. (Chemical Engineering Research & Design, 2015)
Catalytic benzylation of acetic acid (AA) with benzyl alcohol (BA) to benzyl acetate was studied over zeolites viz. H-ZSM-5 (microporous, medium pore), Micro/Meso-HZSM-5 (combination of micro- and meso pore), H-Beta (microporous, large pore) to investigate catalytic activity and selectivity towards benzyl acetate. Micro/Meso-HZSM-5 obtained by desilication post-treatment has been employed as a heterogeneous catalyst for benzylation reaction probably for the first time. Micro/Meso-HZSM-5 was found to be a promising catalyst for benzylation with AA conversion of 94%, selectivity towards benzyl acetate of 95%. The detailed optimization of process parameters such as molar ratio, catalyst loading, reaction temperature and time was also presented. Micro/Meso-HZSM-5 catalyst was observed to be stable for six cycles (1 fresh and 5 recycles). The first order reaction kinetics (R-2 >0.98) indicated that reaction rate constants increased with increasing reaction temperature. The activation energy for benzylation of AA with BA over Micro/Meso-HZSM-5 was obtained to be 15.07 kJ mol(-1), which is far less than the reported. (C) 2014 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acetic acid; Benzyl acetate; Benzyl alcohol; Benzylation; Micro/Meso-HZSM-5; Reaction kinetics